Nancy-Thermal : les rêves de grandeur d’une station luxueuse et populaire - Claire Guitton (UMR 5136- France, Amériques, Espagne – Sociétés, Pouvoirs, Acteurs (FRAMESPA), 2021)
Built between 1912 and 1914 according to the plans of architect Louis Lanternier, the Nancy-Thermal station is a relatively unknown complex. If, with hindsight, the establishment falls under the category of secondary thermal spas, Nancy-Thermal was conceived with the ambition of establishing itself as a first-class unit intending to compete with the nearby great Vosges thermal complexes. Composed of luxurious thermal baths and a large thermal water swimming pool designed as municipal baths, this establishment constitutes an atypical ensemble due to its location in an urban environment and its different target audiences. The outbreak of the First World War interrupted the work, depriving the station of the expected fame. However, despite periods of difficulty, thermal activity has never ceased and continues to this day. Recognized for its architectural interest and its singularities, the Belle-Epoque ensemble has been registered as historical monument since November 3, 2020.